Mindfulness, Depression and Modes of Mind - Williams, J (2008)
The author introduces the special section on mindfulness: four articles that between them explore the correlates of mindfulness in both cross-sectional and treatment studies. Results from these studies, taken together, suggest a close association between higher levels of mindfulness, either as a trait or as cultivated during treatment, and lower levels of rumination, avoidance, perfectionism and maladaptive self-guides. These four characteristics can be seen as different aspects of the same 'mode of mind', which prioritizes the resolution of discrepancies between ideas of current and desired states using a test-operate-test-exit sequence. Mindfulness training allows people to recognize when this mode of mind is operating, to disengage from it if they choose, and to enter an alternative mode of mind characterized by prioritizing intentional and direct perception of moment-by-moment experience, in which thoughts are seen as mental events, and judgemental striving for goals is seen, accepted and 'let go'. © 2008 Springer Science+Business Media, LLC.